The Driving Factors, Mechanism and Result Effects of Entrepreneurial Bricolage From the Perspective of Different Entrepreneurial Contexts (Asian Business Research, 2026)
Entrepreneurship bricolage is an important way for entrepreneurs to dynamically tap and use existing resourcesto achieve the purpose of entrepreneurial activities based on the entrepreneurial context. The research on theresult effect, driving factors and mechanism of entrepreneurship bricolage in different entrepreneurial contextscan provide a new perspective for the effective use of resource endowments for entrepreneurial enterprises. Asystematic analysis of 115 documents collected in the field of entrepreneurial bricolage in recent years found thatthe driving factors of entrepreneurial bricolage from the perspective of different entrepreneurial contexts differdepending on the growth stage and resource endowment status of the enterprise; There are differences in themechanism of entrepreneurial bricolage from the perspective of different entrepreneurial contexts in the macroentrepreneurial environment, the meso entrepreneurial organization, and the micro entrepreneurial individual;The effect of entrepreneurial bricolage from the perspective of different entrepreneurial contexts is different intwo aspects about research theme and research purpose. The research conclusions are helpful for domesticscholars to put forward countermeasures and suggestions to promote the high-quality development of regionalinnovative and entrepreneurial enterprises based on the current status of research in the field of entrepreneurialbricolage, combined with factors such as China's current economic background and entrepreneurial situationdifferences.